Aligned Heterointerface‐Induced 1T‐MoS2 Monolayer with Near‐Ideal Gibbs Free for Stable Hydrogen Evolution Reaction. Issue 8 (30th January 2019) - Zhang, Kan; Jin, Bingjun; Gao, Yujie; Zhang, Shengli; Shin, Hyunjung; Zeng, Haibo; Park, Jong Hyeok
Abstract: 1T‐phase molybdenum disulfide (1T‐MoS2 ) exhibits superior hydrogen evolution reaction (HER) over 2H‐phase MoS2 (2H‐MoS2 ). However, its thermodynamic instability is the main drawback impeding its practical application. In this work, a stable 1T‐MoS2 monolayer formed at edge‐aligned 2H‐MoS2 and a reduced graphene oxide heterointerface (EA‐2H/1T/RGO) using a precursor‐in‐solvent synthesis strategy are reported. Theoretical prediction indicates that the edge‐aligned layer stacking can induce heterointerfacial charge transfer, which results in a phase transition of the interfacial monolayer from 2H to 1T that realizes thermodynamic stability based on the adhesion energy between MoS2 and graphene. As an electrocatalyst for HER, EA‐2H/1T/RGO displays an onset potential of −103 mV versus RHE, a Tafel slope of 46 mV dec −1 and 10 h stability in acidic electrolyte. The unexpected activity of EA‐2H/1T/RGO beyond 1T‐MoS2 is due to an inherent defect caused by the gliding of S atoms during the phase transition from 2H to 1T, leading the Gibbs free energy of hydrogen adsorption (ΔGH* ) to decrease from 0.13 to 0.07 eV, which is closest to the ideal value (0.06 eV) of 2H‐MoS2 . The presented work provides fundamental insights into the impressive electrochemical properties of HER and opens new avenues for phase transitions at 2D/2D hybrid interfaces. Abstract : The hydrogen evolution reaction from 1T‐MoS2 exhibits high efficiency but suffers from durability problems. The 1T‐MoS2 monolayer at the edge‐aligned 2H‐MoS2 and N‐RGO interface shows stable and highly efficient electrochemical properties for the hydrogen evolution reaction (HER) in acidic electrolyte.